Tofacitinib versus methotrexate in rheumatoid arthritis: patient-reported outcomes from the randomised phase III ORAL Start trial. Issue 2 (28th September 2016) - Strand, Vibeke; Lee, Eun Bong; Fleischmann, Roy; Alten, Rieke E; Koncz, Tamas; Zwillich, Samuel H; Gruben, David; Wilkinson, Bethanie; Krishnaswami, Sriram; Wallenstein, Gene
Abstract : Objectives: To compare patient-reported outcomes (PROs) in methotrexate (MTX)-naive patients (defined as no prior treatment or ≤3 doses) receiving tofacitinib versus MTX. Methods: In the 24-month, phase III, randomised, controlled, ORAL Start trial (NCT01039688 ), patients were randomised 2:2:1 to receive tofacitinib 5 mg two times per day (n=373), tofacitinib 10 mg two times per day (n=397) or MTX (n=186). PROs assessed included Patient Global Assessment of disease (PtGA), pain, Health Assessment Questionnaire-Disability Index (HAQ-DI), Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F) and health-related quality of life (Short Form-36 [SF-36]). Results: PROs improved following tofacitinib and MTX treatment: benefits were sustained over 24 months. Patients receiving tofacitinib reported earlier responses which were significantly different between each tofacitinib dose and MTX at month 3 through month 24. At month 6 (primary end point), significant improvements versus MTX were observed in PtGA, pain, HAQ-DI, SF-36 Physical Component Summary (PCS), 5/8 domain scores and FACIT-F with tofacitinib 5 mg two times per day; all PROs, except SF-36 Mental Component Summary Score and Medical Outcomes Survey-Sleep, with tofacitinib 10 mg two times per day. At month 6, the proportion of patients reporting improvements ≥minimum clinically important difference were significant versus MTX with tofacitinib 5 mg two times per day in PtGA and 3/8 SF-36 domains; and with tofacitinib 10 mg two times per day in PtGA, pain, HAQ-DI, SF-36 PCS, 4/8 domains and FACIT-F. Conclusions: Patients with rheumatoid arthritis receiving tofacitinib 5 and 10 mg two times per day monotherapy versus MTX reported statistically significant and clinically meaningful improvements in multiple PROs over 24 months; onset of benefit with tofacitinib treatment occurred earlier. Trial registration number: NCT01039688.